2022
DOI: 10.3389/fcimb.2022.840968
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Red Blood Cell-Specific Glycolytic Intermediate 2,3-Diphosphoglycerate (2,3-DPG) Inhibits Plasmodium falciparum Development In Vitro

Abstract: Mechanisms of malaria parasite interaction with its host red blood cell may provide potential targets for new antimalarial approaches. Pyruvate kinase deficiency has been associated with resistance to malaria in both experimental models and population studies. Two of the major pyruvate kinase deficient-cell disorders are the decrease in ATP and the increase in 2,3-biphosphoglycerate (2,3-BPG) concentration. High levels of this metabolite, only present in mammalian red blood cell, has an inhibitory effect on gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 49 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…These effects on the deformability of noninfected cells and on the RBC zeta potential were not sufficient to impair the efficient reinvasion of new RBCs upon exposure to 2,3-DPG. Thus, it cannot significantly contribute to the substantial decrease in the number of parasites that start the following cycle, as previously observed [ 15 ]. However, in the reinvasion assay, there was never a mixture with 2,3-DPG between the initial culture conditions before the magnetic selection of mature parasites, and the second condition in which the enriched parasites were re-cultured in previously treated RBC, by then washed and cultured in a medium without 2,3-DPG addition.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…These effects on the deformability of noninfected cells and on the RBC zeta potential were not sufficient to impair the efficient reinvasion of new RBCs upon exposure to 2,3-DPG. Thus, it cannot significantly contribute to the substantial decrease in the number of parasites that start the following cycle, as previously observed [ 15 ]. However, in the reinvasion assay, there was never a mixture with 2,3-DPG between the initial culture conditions before the magnetic selection of mature parasites, and the second condition in which the enriched parasites were re-cultured in previously treated RBC, by then washed and cultured in a medium without 2,3-DPG addition.…”
Section: Discussionmentioning
confidence: 84%
“…We have been investigating how the glycolytic metabolite 2,3-DPG may be involved in the protective effect against malaria caused by PKD. Morais et al [ 15 ] showed that, when 2,3-DPG 8 mM was added daily into a culture medium, there was a sharp reduction in parasite densities and a reduction in parasite progeny at the end of an intraerythrocytic developmental cycle. Furthermore, a shift of the metabolic profile of iRBC treated with 2,3-DPG, making it closer to that of niRBC, was observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations